Predicting Firms’ Financial Distress: A Case Study - Samirah Dunakhir (PINISI Discretion Review, 2023)
This study aims to predict the company's financial condition related to financial distress. The analysis was carried out during the COVID-19 pandemic, specifically for coal mining companies listed on the Indonesia Stock Exchange (IDX). The annual financial reports of coal mining companies during the COVID-19 pandemic were collected and analyzed using Altman Z-Score models. The result shows that most of the companies are in the distress category. This shows that the COVID-19 pandemic situation has also hit large companies in Indonesia.